PERANCANGAN APLIKASI PELAYANAN CLEANING SERVICE BERBASIS WEB - Ariyadi Armi; Yeka Hendriyani (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
Problems that occur in a service can be seen in a business process carried out. Customer service, management of orders, promotions, and other services, whether it is a main process or a supporting process. In service business this service still uses social media. In business reporting, running is still done manually. To provide good results on this service, the system requires web-based e-commerce to help all who will run the service business process. With the existence of e-commerce services can facilitate existing promotions. This e-commerce system service uses the MVC model (Model, View, Controller). The programming language used is the programming language PHP (PHP Hypertext Preprocessor) and uses the Laravel framework and MySQL as a Database Management System (DBMS) and Sublime Text 3 as supporting editors. Business processes that exist in this service can cover a wider area in order to convey information to consumers and facilitate customer access in ordering services.Keywords :Laravel Framework, MySQL, E-Commerce.